STRATEGI DINAS KESEHATAN KOTA PEKANBARU DALAM PENCEGAHAN HUMAN IMMUNODEFICIENCY VIRUS (HIV) DI KOTA PEKANBARU TAHUN 2022 - Hati, Rezi Fortuna; ', Wazni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Human Immunodeficiency Virus (HIV) is a type of virus that attacks/infects white blood cells which causes a decrease in human immunity due to immune deficiency. In 2022, the number of HIV cases in Pekanbaru City will experience a spike with 255 cases. Handling the health sector is one of the mandatory matters related to basic services for the city government. The aim of this research is to determine the strategy of the Pekanbaru City Health Service in preventing Human Immunodeficiency Virus (HIV) disease in Pekanbaru City. This research uses a qualitative approach. The types of data are primary data and secondary data, primary data is obtained directly from informants. Meanwhile, secondary data is data that supports or strengthens primary data. Data collection techniques use interviews and documentation studies. And data analysis uses data reduction, data presentation, and drawing conclusions. The research results show the strategy implemented by the Pekanbaru City Health Service. First, a preventive strategy to prevent the spread of HIV by providing outreach, mother-to-child prevention, HIV testing and counseling services. Second, innovative HIV prevention strategies in the form of new innovations carried out by the Limapuluh Community Health Center, namely the GOCAP clinic (Voluntary Counseling Test Anti-Difference Movement) and Extra Time services. Keywords: Government Strategy, Prevention, Human Immunodeficiency Virus